Monitoring of radiation situation in the territory of the Voronezh region - Yu. I. Stepkin; M. K. Kuzmichev; O. V. Klepikov (Радиационная гигиена)
The purpose of the study was to assess the doses of personnel and the population at the expense of all the main activities and sources of radiation in the territory of the Voronezh region. The data of the forms of state statistical supervision No. 1-DOZ “Information on the doses of personnel from persons under normal use of technogenic sources of ionizing radiation”, No. 3-DOZ “Information on radiation doses of patients during X-ray radiology studies”), No. 4-DOZ “Information on radiation doses of the population due to natural and technogenically altered background” for 2010-2016 and the radiation and hygienic passport of the territory of the Voronezh Region. Based on the results of monitoring the radiation situation, the situation associated with the impact of ionizing radiation sources in the Voronezh Region has been characterized as safe for the past 7 years. The average annual effective dose per 1 inhabitant due to all ionizing radiation remains stable with a slight upward trend and lies in the range from 2.925 (2010) to 3.399 mSv (2016). In the structure of the collective dose of the population of the Voronezh region, the dose from natural sources is 83.65%, from medical sources – 16.06%, from technogenically changed background radiation, including global fallout and accident at the Chernobyl nuclear power plant – 0.18%, from the activities of enterprises using Sources of ionizing radiation – 0.11%. The average annual effective dose of natural exposure to humans varies from 0.660 to 0.704 mSv / year, natural radiation from radon from 0.832 to 1.465 mSv / year. The average effective dose from medical research for the procedure for the study period was 0.27-0.40 mSv and tends to decrease due to the introduction of modern low-dose medical diagnostic equipment. On the territory of the Voronezh region, there were no population groups with an effective radiation dose exceeding 5 mSv / year. Gamma-background in the region in 2010-2016. Did not exceed the natural level and amounted to 0.08 – 0.16 μSv / h. The excess of hygienic standards for the effects of ionizing radiation sources on humans has not been recorded.